Additivity of semantic and phonological effects: Evidence from speech production in Mandarin. Issue 11 (1st November 2016) - Zhu, Xuebing; Zhang, Qingfang; Damian, Markus F.
Abstract : A number of previous studies using picture–word interference (PWI) tasks conducted with speakers of Western languages have demonstrated non-additive effects of semantic and form overlap between pictures and words, which may indicate underlying non-discrete processing stages in lexical retrieval. The present study used Mandarin speakers and presented Chinese characters as distractors. In two experiments, we crossed semantic relatedness with "pure" phonological (i.e., orthographically unrelated) relatedness and found statistically additive effects. In a third experiment, semantic relatedness was crossed with orthographic overlap (phonological overlap was avoided), and once again we found an additive pattern. The results are discussed with regard to possible cross-linguistic differences between Western and non-Western languages in terms of phonological encoding, as well as concerning the locus of relatedness effects in PWI tasks.